PURSUANCE AND THE PRACTICE OF DE-INSTITUTIONALIZED DEMOCRACY - Tynes, Robert; Peters, Claire (AoIR Selected Papers of Internet Research, 2018)
The internet offers the possibility of forming de-institutionalized, organizational structures that engage in the democratic process in ways that go far beyond volunteering, protesting, or voting. The digital space enables people to collaborate and communicate with one another more effectively, even if they have never met in real life (Shirky 2009). Formations such as Telecomix and Project PM show that this capability can be harnessed in the service of meaningful collective political and social actions. Journalist and activist Barrett Brown's latest venture, $2 , hopes to further that potential. Pursuance looks to empower political actors via "process democracy" (Brown 2018), offering participants a platform in which they can organize, build, and act on social justice endeavors. Pursuance is important because it provides a means for individuals to rapidly and effectively assemble, disassemble, and reassemble into mission-driven teams. This lessens the need for stable institutions to direct civic or political activism, thus reducing the problems that often follow, e.g. the Iron Law of Oligarchy (Michels 2015). We explore the potential of Brown's endeavor, asking: How can Pursuance most effectively further the practice of deinstitutionalized democracy? What can be learned from past groups that have engaged in the kind of activity Pursuance aims to facilitate?